Knowledge and Practice of Healthcare Workers Regarding the Healthcare Waste Management - Tikka Khan Faisal, Gulnaz Banu, Shagufta Emmanuel, Jacollin George, Farah Naz, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Healthcare waste management (HWM) issues are getting worse in Pakistan since there are more and more hospitals, clinics, diagnostic labs, etc. One of the major individuals in charge of properly managing healthcare wastes at any healthcare facility is the medical staff. But how well you perform will rely on how much you know and do about waste management. Aim: To ascertain the knowledge and practice of healthcare professionals about the management of healthcare waste. Study design: Cross-sectional descriptive study. Methodology: The Children Hospital Lahore has conducted the current study. The current study included 400 participants. Structured, pre-tested, and self-administered questionnaires were used to collect data. The survey was cleaned, revised, and reviewed for completeness. The analysis of the data was done using SPSS 23. Results: 400 individuals were involved, 174(43.5%) of whom had sufficient understanding of health care waste management, whereas 226(56.5%) had insufficient knowledge. Of the 400 participants, 188(47%) had good practice managing medical waste, whereas the remaining 212(50%) had bad practice. Practical Implication: This study helped researchers investigate the knowledge and practice of health workers. It would help in estimating the practice and knowledge of health waste management by health care workers. Conclusion: It was determined that most workers had inadequate knowledge of waste management and had poor practice on health care waste management. All employees must receive the appropriate training and supervision in HCW management, as well as pertinent and continuous in-service training, to ensure that they have the necessary information, attitudes, and safe practices. Keywords: Health Care Workers, Waste Management, Knowledge, Practices and Training.